Caught stealing [videorecording (Blu-Ray)] - Huston, Charlie; Butler, Austin, 1991-; King, Regina; Kravitz, Zoë, 1988-; Smith, Matt, 1982-; Schreiber, Liev; D'Onofrio, Vincent; Bad Bunny, 1994-; Dunne, Griffin; Kane, Carol, 1952-; Libatique, Matthew, 1969-; Simonsen, Rob, 1978-; et al. (Sony Pictures Home Entertainment, 2025)
"Hank Thompson was a high school baseball phenom who can't play anymore, but everything else is going okay. He's got a great girl, tends bar at a New York dive, and his favorite team is making an underdog run at the pennant. When his punk-rock neighbor Russ asks him to take care of his cat for a few days, Hank suddenly finds himself caught in the middle of a motley crew of threatening gangsters. They all want a piece of him; the problem is he has no idea why. As Hank attempts to evade their ever-tightening grip, he's got to use all his hustle to stay alive long enough to find out."--